2023
DOI: 10.3390/heritage6020058
|View full text |Cite
|
Sign up to set email alerts
|

The Mortella II Wreck, a Genoese Merchantman Sunk in 1527 in Corsica (Saint-Florent, France): A Preliminary Assessment of the Site, Hull Structures and Artefacts

Abstract: This article presents the results of a preliminary archaeological operation carried out in 2021 on the Mortella II wreck. It was designed as a continuation and complement to the excavation of the Mortella III wreck that was performed between 2010 and 2019 and to which it is historically linked: both ships were Genoese merchantmen sailing together, which sunk in 1527 in the context of the 7th Italian War between France and Spain. The paper takes up the main outcomes of the lines of research on shipbuilding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The second part of this contribution is instead dedicated to an in-depth study of the finding of the underwater excavation carried out in 2021 in northern Corsica at the site of the Mortella II wreck, a Genoese commercial ship that sunk in 1527, and investigated by an international team led by Arnaud Cazenave de la Roche [2].…”
Section: Introductionmentioning
confidence: 99%
“…The second part of this contribution is instead dedicated to an in-depth study of the finding of the underwater excavation carried out in 2021 in northern Corsica at the site of the Mortella II wreck, a Genoese commercial ship that sunk in 1527, and investigated by an international team led by Arnaud Cazenave de la Roche [2].…”
Section: Introductionmentioning
confidence: 99%
“…Two more articles refer to another important underwater Early Modern archaeological site. "The Mortella II Wreck, a Genoese Merchantman Sunk in 1527 in Corsica (Saint-Florent, France): A Preliminary Assessment of the Site, Hull Structures and Artefacts" [5] is the full study of the two wrecks of "La Mortella II and III" located in Corsica. The study is completed by the article "Post-Medieval Wrecks in the Western Mediterranean and Pottery: The Mortella II Wreck (1527) and the Chronology of Montelupo Tin-Glazed Earthenware" [6], which includes a preliminary study of the ceramics found in the 2021 excavation that was conducted in the area of the wreck of the Mortella II.…”
mentioning
confidence: 99%